Hotel Business Sustainability Strategy in Bogor Raya - Sukma, Braja Eka; Maudiarti, Santi; Pramanik, Purwanti Dyah (Technium Social Sciences Journal, 2025)
Every business owner hopes their business will grow, develop, and remain sustainable. To achieve this, an effective strategy is necessary for operating a business. This study aims to analyse the external aspects of the hotel business related to efficiency policies. The research method used a quantitative research design. The population consisted of 18 member hotels of the Indonesia Hotel General Manager Association (IHGMA) in Bogor Raya, with a saturated sample. The results found that the Question Marks strategy is an appropriate approach for hotel businesses in Greater Bogor to maintain sustainability. The implications of the research results are optimising revenue from existing products or services, carrying out self-improvement, while waiting for the situation to improve.